Особливості лікування диференційованого раку щитоподібної залози, що його було виявлено у пацієнток під час вагітності - Черенько, С. М.; Ларін, О. С.; Федорченко, Г. А.; Давидова, Ю. В. (Clinical Endocrinology and Endocrine Surgery, 2012)
Data about treatment of 47 pregnant women with differentiated thyroid carcinoma (DTC), diagnosed and operated on during pregnancy within 1996-2011 years in specialized hospital were given in the article. For 20 patients from "low risk group" (Ò1-2N0M0) was proposed and done new less aggressive approach providing abandon of radioiodine ablation after delivery if serum thyroglobulin gradually dropped down till 4-6 months after operation to lower level of detection at the absence of thyroglobulin antibodies and sonographic signs of lymph node metastases. Meanwhile, high risk of neck metastases of DTC in pregnant women (49%) needs to provide more aggressive initial surgical operation including not only extracapsular total thyroidectomy but prophylactic central (for some indications – lateral as well) lymph node neck dissection for proper disease staging, adequate choice of treatment options and diminishing of relapses.